PHARMACOKINETIC PROFILE OF LUMBAR EPIDURAL BUPIVACAINE INJECTION IN PREECLAMPSIA PATIENTS DURING CESAREAN SECTION: CASE STUDY IN DR. SARDJITO HOSPITAL YOGYAKARTA - Helmina Wati; Djoko Wahyono; Farida Hayati; Yusmein Uyun (Faculty of Pharmacy, Universitas Gadjah Mada)
Preeclamsia patient experienced deterioration of glomerolus filtration and plasma protein concentration. Bupivakain is bound strongly with the plasma protein that is 95%. This research was aimed to know the pharmacokinetics profiles of isobaric bupivacaine with the noncompartemen model in preeclampsia patients who underwent Sectio Caesarea (SC) with lumbar epidural technique in RSUP Dr. Sardjito and to know correlation between protein levels and pharmacokinetics profiles of isobaric bupivacaine in preeclampsia patients. Firstly, albumin concentration of patients was checked in the laboratory and then isobaric bupivacaine 0.5% in 15ml (75mg) was given by lumbar epidural technique. The samples of blood were taken through veins vessels at 0; 15; 20; 25; 30; 45; 60 and 90 minutes. The concentration of 0.5% isobaric bupivacaine in those samples of blood was determined with High Performance Liquid Chromatography (HPLC) methods. Furthermore, pinprick test was taken to measure block sensoric effect in T10-T6 areas. Pharmacokinetics parameters of bupivacaine (AUC, AUMC, MRT) were calculated based on data of bupivakain concentration in the blood versus time. The results of this research showed that the AUC0-∞ (total AUC) was 116±37,6 (μg/ml) minutes; AUMC0-∞ (total AUMC) was 9187,5 (μg/ml) minutes2; and MRT0-∞ was 102,5 minutes. Average block sensoric effect was at T8. There was no linear correlation between the protein levels and pharmacokinetics profiles of bupivacaine (p>0,05). The conclusion was that there was no linear correlation between the protein levels and pharmacokinetics profiles of bupivacaine that was given by lumbar epidural in preeclampsia patientswho underwent section caesarea.Keywords : bupivakaine, pharmacokinetic profile, lumbar epidural, section caesarea.